Crossectional survey; Assessment of Diarrheal Disease Prevalence and the Associated Factors among Children under Five in Enemay District, Northwest Ethiopia (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: diarrhea; two week prevalence; ethiopia